The Influence of Atomic Metal Conditioner Additive with Surface Revitalizer on the Lubricating Properties of Engine Oil - Ruslans Smigins; Audrius Žunda; Albinas Andriušis; Çağla Gizem Acar; Simona Tučkutė (Lubricants, 2025)
The development of multifunctional lubricant additives is critical for enhancing the performance and longevity of internal combustion engines. This study investigates the influence of oil additive, containing an atomic metal conditioner (AMC), a two-dimensional sliding agent, and a patented revitalizer on lubricating properties of engine oil 5W-30 and on surface wear characteristics. The experimental testing involved comparative tribological evaluation using the 4-ball test. Pure commercial engine oil (PEO) 5W-30 and oil mixed with the revitalizer additive (OMA) were used. The changes in friction torque (FTq), temperature, and wear scars were analyzed. FTq evolution showed a distinct behavior across the different test cases: PEO exhibited fluctuating FTq in the initial minute and thereafter, but its value was lower, and the wear scars were smaller compared to OMA. Long-duration tests revealed that OMA resulted in significantly larger wear scars, large FTq values, and less variations emerging later in the test. When switching from PEO (1 h) to OMA (1 h) mid-test, the wear increased compared to 2 h PEO. Across all conditions, oil temperature had a strong relationship with FTq. Although some frictional improvements were observed, no definitive evidence of revitalizer-induced surface regeneration was detected, suggesting adhesive wear remained predominant under the studied conditions.